2022
DOI: 10.3390/diagnostics12061480
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Learning Based on Multiple Descriptors for WSIs Diagnosis

Abstract: An automatic pathological diagnosis is a challenging task because histopathological images with different cellular heterogeneity representations are sometimes limited. To overcome this, we investigated how the holistic and local appearance features with limited information can be fused to enhance the analysis performance. We propose an unsupervised deep learning model for whole-slide image diagnosis, which uses stacked autoencoders simultaneously feeding multiple-image descriptors such as the histogram of orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…In the aftermath of lung cancer surgery, the postoperative period unfolds as a critical phase where AI demonstrates its potential in pathological assessment. A multitude of studies, such as those by Sheikh ( 36 ) and DiPalma et al. ( 37 ), accentuate the role of DL methodologies in detailed histological subtyping.…”
Section: Postoperative Periodmentioning
confidence: 99%
See 4 more Smart Citations
“…In the aftermath of lung cancer surgery, the postoperative period unfolds as a critical phase where AI demonstrates its potential in pathological assessment. A multitude of studies, such as those by Sheikh ( 36 ) and DiPalma et al. ( 37 ), accentuate the role of DL methodologies in detailed histological subtyping.…”
Section: Postoperative Periodmentioning
confidence: 99%
“…Sheikh et al. ( 36 ) explored the impact of multiple descriptors on a deep learning model’s performance in the multi-class classification of WSIs. They found that augmenting inputs enhanced the discriminatory capabilities of the model.…”
Section: Postoperative Periodmentioning
confidence: 99%
See 3 more Smart Citations